2022
DOI: 10.1039/d2cb00168c
|View full text |Cite
|
Sign up to set email alerts
|

A multicomponent reaction platform towards multimodal near-infrared BODIPY dyes for STED and fluorescence lifetime imaging

Abstract: We report a platform combining multicomponent reaction synthesis and automated cell-based screening to develop biocompatible NIR-BODIPY fluorophores. From a library of over 60 fluorophores, we optimised compound NIRBD-62c as a...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…Structurally, it is the simplest of the NIR-AZA uorophore class, which is more commonly further derivatised to suit a diverse set of biological and material purposes. [8][9][10][11][12][13][14][15][16][17] Previously we have shown that 1 and P 188 spontaneously undergo a DSA in water to form nanoparticles NP1-P 188 of ∼100 nm size with the uorescence from 1 quenched (Fig. 1C).…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…Structurally, it is the simplest of the NIR-AZA uorophore class, which is more commonly further derivatised to suit a diverse set of biological and material purposes. [8][9][10][11][12][13][14][15][16][17] Previously we have shown that 1 and P 188 spontaneously undergo a DSA in water to form nanoparticles NP1-P 188 of ∼100 nm size with the uorescence from 1 quenched (Fig. 1C).…”
Section: Introductionmentioning
confidence: 86%
“…Structurally, it is the simplest of the NIR-AZA fluorophore class, which is more commonly further derivatised to suit a diverse set of biological and material purposes. 8–17…”
Section: Introductionmentioning
confidence: 99%
“…12–14 Notably, new technologies such as photoacoustic (PA) and fluorescence lifetime imaging (FLIM) are emerging as promising techniques due to their intrinsic high contrast and multiplexing capabilities. 15–17 The features of smart fluorescent architectures provide a wide range of possibilities in biomedical research, from the interrogation of functional states in vitro to the in vivo evaluation of anti-cancer immunotherapies in preclinical models (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…To develop organic dyes for far-red STED imaging, rigorous physical and biocompatibility requirements must be met, including high photostability, brightness, and no light or dark toxicity [ 2 ]. Recent investigations have shown that rhodamine derivatives, π-extended-BODIPYs, and Nile red fluorophores are STED compatible when used with a 775 nm DL ( Figure 1 ) [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. Achievements have been made in defining subcellular structures, such as the cristae of mitochondria [ 8 , 9 , 10 ] and vimentin filaments [ 13 ] using these dye classes.…”
Section: Introductionmentioning
confidence: 99%